THE ROLE OF INDIVIDUAL COUNSELING SERVICE TO ADDRES BULLYING VICTIMS OF STUDENTS SMK BINA PATRIA 1 SUKOHARJO IN THE ACADEMIC YEAR 2020/2021 - Andriani, Desi; Sri Suryanti, Hera Heru (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The purpose of this research is to know how the role of individual counseling service to address bullying victims of students SMK Bina Patria 1 Sukoharjo in the academic year 2020/2021. In this research, the researcher used qualitative descriptive research. The subject of this research is the students of SMK Bina Patria 1 Sukoharjo. To collected the data, the researcher used interview, observation, and documentation. Inteview techniques are used to obtain direct data from source and clients. Observation is used to obtain data through observations of clients related to activities carried out by clients, and documentation techniques ia to obtain written data and photographic data of client activities. To get the validity of the data, the researcher used triangulation data and method. To analyzed data, The researcher used data collection, data reduction, data display, and drawing conclusion. The result of this research is explain how the role of individual counseling service to reduce victims of bullying at SMK Bina Patria 1 Sukoharjo. Seen from the counseling result, students become less frequent and moody anymore, these changes are felt by clients by filling in more useful and positive activities, so the clients can slowly forget the events they have experienced. Beside that, there are also those that cannot be controlled by the client, namely anxiety, restlessness and lazy to come to school, it cannot be practiced by clients because of the situation and conditions during the pandemic. Keywords : Individual counseling, Bullying victims.